Unmet Needs in the Management of Moderate-to-Severe Psoriasis in Spain: A Multidimensional Evaluation - Néboa Zozaya; Renata Villoro; Fernando Abdalla; Santiago Alfonso Zamora; Jesús Balea Filgueiras; José Manuel Carrascosa Carrillo; Olga Delgado Sánchez; Francisco Dolz Sinisterra; Antonio García-Ruiz; Pedro Herranz Pinto; Antonio Manfredi; José Martínez Olmos; et al. (Medical Journals Sweden, 2022)
Psoriasis is a chronic, systemic inflammatory disease that affects the skin, with a high impact on patients' quality of life. The aim of this study was to identify and determine the relative importance of unmet needs in the management of moderate-to-severe psoriasis in Spain, from a multi-stakeholder perspective. A mixed method-approach was used to collect information, design a questionnaire and a discrete-choice exercise, and elicit the unmet needs through a multidisciplinary committee composed of 12 experts. A total of 65 unmet needs were identified and categorized into 4 areas: clinical, patient-related, decision-making process, and social. Decision-making process unmet needs were perceived as the most pressing ones, followed by social, clinical and patient-related. Individually, the need to incorporate outcomes that are important to the patients and to have treatments that achieve total clearance with a rapid onset of action and long-term persistence were the most important unmet needs.